2002
DOI: 10.1097/01.lab.0000029205.76632.a8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity and Promoter Methylation, but not Mutation, May Underlie Loss of TFF1 in Gastric Carcinoma

Abstract: SUMMARY:It has been advanced that the trefoil factor (TFF) 1 gene is a candidate tumor-suppressor gene and may be involved in the development and/or progression of human gastric cancer. We aimed to clarify the putative role of TFF1 in gastric carcinogenesis. Ninety gastric carcinomas and eight gastric carcinoma-derived cell lines were screened for TFF1 mutations; subsets of the primary tumors and of the cell lines were subjected to loss of heterozygosity (LOH), immunohistochemistry, and promoter methylation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 24 publications
3
76
0
Order By: Relevance
“…Four of the markers used in the present study (D5S818, CSFIPO, D18S51, D21S11) were located in regions which have been shown to be non-randomly lost during the progression of GCA [26] (Table 2). These chromosomal arms, 5q, 18q, and 21q, have been shown to contain the tumor suppressor genes APC and MCC [33], DCC [34], and trefoil factor 1 [35], respectively. Our tetranucleotide markers reported a rate of LOH of about 20% in the corresponding chromosomal region, consistent with previous reports (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Four of the markers used in the present study (D5S818, CSFIPO, D18S51, D21S11) were located in regions which have been shown to be non-randomly lost during the progression of GCA [26] (Table 2). These chromosomal arms, 5q, 18q, and 21q, have been shown to contain the tumor suppressor genes APC and MCC [33], DCC [34], and trefoil factor 1 [35], respectively. Our tetranucleotide markers reported a rate of LOH of about 20% in the corresponding chromosomal region, consistent with previous reports (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…4 -6 We and others have reported that Tff1 expression is remarkably down-regulated in nearly all human gastric cancers. 7,8 Recent reports support the notion that Tff1 may be a candidate tumor suppressor gene that may be involved in development and/or progression of human gastric cancers. 6,7,9 The Tff1 knockout (Ϫ/Ϫ) mouse model was first reported in 1996 as a model for spontaneous development of intestinal-type gastric dysplasia and cancer, similar to human disease.…”
mentioning
confidence: 90%
“…7,8 Recent reports support the notion that Tff1 may be a candidate tumor suppressor gene that may be involved in development and/or progression of human gastric cancers. 6,7,9 The Tff1 knockout (Ϫ/Ϫ) mouse model was first reported in 1996 as a model for spontaneous development of intestinal-type gastric dysplasia and cancer, similar to human disease. 10 Thus, the Tff1Ϫ/Ϫ mouse model provides a window to look into molecular alterations that are associated with precancerous lesions and understand the development of gastric cancers.…”
mentioning
confidence: 90%
“…TFF1 expression is strongly induced after mucosal injury (6) and is involved in stomach ontogenesis and maintenance of the integrity of the mucosa (2, 3). Molecular studies have shown frequent loss of TFF1 expression in more than two-thirds of gastric carcinomas resulting from a mutation-independent mechanism (7)(8)(9). The silencing of the TFF1 gene in gastric carcinomas is due to loss of heterozygosity (LOH) and methylation of the TFF1 promoter region (7,(10)(11)(12)(13), but mutations are seen only in approximately 5% of gastric carcinomas (7,14).…”
Section: Introductionmentioning
confidence: 99%